Development and Usability Analysis of a Multimedia eConsent Solution - Schneiderheinze, Hauke; Prokosch, Hans-Ulrich; Apel, Hendrik; Bellut, Laura; Wullich, Bernd; Trollmann, Regina; Schüttler, Christina (German Medical Data Sciences: Shaping Change – Creative Solutions for Innovative Medicine, 2019)
BACKGROUND: More and more medical data is being stored digitally in routine care. The secondary use of patient data is only possible to a limited extent for data protection reasons. In order to enable a long-term and far-reaching use of secondary data, a possible approach is to obtain "broad consent" from patients, e.g. on research projects whose purpose is still unknown at the time of consent. OBJECTIVE: To develop and evaluate an interactive eConsent prototype that presents the extensive contents of the "broad consent" in multimedia form for the purpose of a successful and resource-efficient information and consent process. METHODS: The eConsent prototype was designed on basis of a literature review and in accordance with the goals of the German medical informatics initiative. User tests and subsequent questionnaire surveys using the System Usability Scale (SUS) were carried out with patients from a university hospital to assess the prototype's usability. The study was conducted in a quasi-experimental, one-group posttest-only design. RESULTS: The created interactive prototype can present the contents acoustically and visually and offers the possibility to retrieve additional information. With a SUS score of 84,1/100 the results indicate a very good usability of the prototype. CONCLUSION: The next steps will include further refinements of the prototype based on the feedback received and a subsequent study with a broader user group aimed at introducing an eConsent tool as part of a patient portal.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Informed consent; multimedia; patient participation; patient portals